Método para detectar estructuras riesgosas - Ramírez de Alba, Horacio; Gómez Rivera, Sebastían; Neri González, Javier (CIENCIA ergo-sum; Vol. 1 Núm. 1 (1994): CIENCIA ergo-sum (marzo-junio 1994), 2017)
-